Gastronomic culture: Innovation plus services - Manzano - Ascanio, Cristhian Alfonso; Pacheco - Sánchez, Carlos Alberto (Universidad Francisco de Paula Santander, 2018)
The gastronomic sector it promotes the organizational development and the construction of actions in favor of a regional identity, therefore, the investigation had as objective to know about the gastronomic culture in the municipality of Ocaña, identifying in a previous way the characteristics, the satisfaction and the preferences of the consumer, achieving from a quantitative study to apply the technique of the survey to the consumers who habitually attend the restaurants of the central zone, However, with the results obtained from the questionnaires, it was analyzed that gastronomy does not have innovation, with this it recommends to the sector to implement a specialized gastronomy that builds a change in the feeding and allows to create in the palate of the consumer identity through the offer of local, national and international foods.